Advanced learning tools for students with attention deficit hyperactivity disorder - Nor Azlina Ab. Aziz; Kamarulzaman Ab. Aziz; Anuar Mohd Yusof; Avijit Paul (2012)
Providing education for students with attention deficit hyperactive disorder (ADHD) is a challenge. These students need a special approach compared to normal students. They are known to have limited attention span and easily distracted. One way information sharing where an instructor is the source of information is not suitable for them. A learning module that can simulate their interest and catch their attention is needed to ensure an effective learning session. Therefore this paper look into possibilities of adopting advance learning tools in enhancing education system for students with ADHD. The tools are believed to be able to spark their curiosity and grab their attention, which is the main challenge in educating students with ADHD. A study was conducted to see the teachers' opinion regarding the pros and cons of the adoption of these tools, whereas a second study was done to observe the students response. From the two studies conducted we are positive that the special education students, particularly students with ADHD, can also benefit from the application of advance learning tools. In addition to academic purpose, the students' social and problem solving skills can also be improved through adoption of these tools.